(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the response of integrated nutrient management and micronutrients on quality, nutrient content, nutrient uptake and soil parameters of tomato at College of Agriculture, Anand Agricultural University, Vaso, during rabi season in 2019-20 and 2020-21. The randomized block design with factorial concept having 14 treatment combinations with three replications comprising two factors having two levels of micronutrients and seven levels of INM was used. Different treatments of INM and micronutrients improved the quality, nutrient uptake and soil parameters. The maximum titrable acidity (0.92%) recorded with M1: zinc@ 100 & N6: 50% RDF + 50% N from vermicompost + bio NPK, while maximum TSS (5.38 oBrix), lycopene (3.08 mg/100 g) and vitamin-C (34.93 mg/100 g) recorded with N6. For nutrient uptake, M1: zinc @ 100 ppm recorded maximum nitrogen uptake by plant (119.71 kg/ha). In INM, treatment N5 recorded maximum nitrogen content (1.72%), phosphorus (0.68%), potash (1.38%), nitrogen uptake (125.75 kg/ha), phosphorus uptake (44.42 kg/ha) and potash uptake (54.95 kg/ha). The INM treatment N5: 50% RDF + 50% N from FYM + Bio NPK recorded maximum microbial count (6.2 × 107 and 7.5 × 107)during 2019-20 and 2020-21, respectively and also maximum available N2O (271.77 kg/ha), available P2O5 (51.08 kg/ha), available K2O (257.13 kg/ha), organic carbon (0.45%), minimum electrical conductivity (1.13 dS/m) and pH (7.76).